Case Report: Long-term survival of a patient with advanced rectal cancer and multiple pelvic recurrences after seven surgeries - Ouyang, Ye; Zhu, Yilin; Chen, Haoyi; Li, Guoquan; Hu, Xiongwei; Luo, Hongyu; Li, Zhou; Han, Shuai (Frontiers in Oncology, 2023)
Abstract Background: Rectal cancer has a high risk of recurrence and metastasis, with median survival ranging from 24 months to 36 months. K-RAS mutation is a predictor of poor prognosis in rectal cancer. Advanced rectal cancer can be stopped in its tracks by pelvic exenteration. Case summary: A 51-year-old woman was diagnosed with advanced rectal cancer (pT4bN2aM1b, stage IV) with the KRAS G12D mutation due to a change in bowel habits. The patient had experienced repeated recurrences of rectal cancer after initial radical resection, and the tumor had invaded the ovaries, sacrum, bladder, vagina and anus. Since the onset of the disease, the patient had undergone a total of seven surgeries and long-term FOLFIRI- or XELOX-based chemotherapy regimens, with the targeted agents bevacizumab and regorafenib. Fortunately, the patient was able to achieve intraoperative R0 resection in almost all surgical procedures and achieve tumor-free survival after pelvic exenteration. The patient has been alive for 86 months since her diagnosis. Conclusions: Patients with advanced rectal cancer can achieve long-term survival through active multidisciplinary management and R0 surgery.